DINAMIKA STRUKTURAL FUNGSIONAL DALAM EKSISTENSI USAHA PATUNG BATU ANDESIT DI DUSUN JATISUMBER, KABUPATEN MOJOKERTO - Sari, Devy Agustin; Yuniar, Ananda Dwitha; Hadi, Nur; Perguna, Luhung Achmad (UNIVERSITAS SEBELAS MARET (UNS), 2023)
Most of the people of Jatisumber Hamlet work as craftsmen of andesite stone statues. However, the occurrence of various problems led to a decrease in the number of andesite stone sculpture craftsmen in Jatisumber Hamlet. The purpose of this research is to analyze the structural-functional dynamics in the existence of the andesite stone sculpture business in Jatisumber Hamlet. This study applies a qualitative research method with a descriptive approach. The research location is in Jatisumber Hamlet, Watesumpak Village, Trowulan, Mojokerto. Data collection techniques were obtained from non-participant observation, structured interviews, and documentation. The results of this study found that the decline in andesite stone sculpture craftsmen in Jatisumber Hamlet was caused by the 1st Bali bombing incident in 2002, the place where cast statues were made in Jatisumber Hamlet in 2005, and the global economic crisis in 2008. Craftsmen who did not continue their business could change professions or become sculptors andesite stone statues in other places of business, so that only a few of the andesite stone sculpture craftsmen remained who decided to survive. The craftsmen who survived implemented 10 adaptation strategies to overcome obstacles and maintain the andesite stone sculpture business. As with the structural-functional theory from Talcott Parsons that the decline of craftsmen forms a system in the andesite stone sculpture business, the roles of craftsmen and sculptors are interrelated in the system. So that part of AGIL is carried out so that the system can survive which includes: determining 10 adaptation strategies (adaptation), adaptation strategies are applied to achieve goals (goal attainment), implementation of adaptation strategies through cooperation (integration), maintaining andesite stone sculpture business by implementing strategies adaptation (latency).Keywords: Craftsmen, Adaptation Strategy, Andesite Stone Sculpture Business AbstrakSebagian besar masyarakat Dusun Jatisumber berprofesi sebagai pengrajin patung batu andesit. Namun terjadinya berbagai permasalahan menyebabkan semakin menurunnya jumlah pengrajin patung batu andesit di Dusun Jatisumber. Tujuan dari penelitian ini untuk menganalisis dinamika struktural fungsional dalam eksistensi usaha patung batu andesit di Dusun Jatisumber. Penelitian ini menerapkan metode penelitian kualitatif dengan pendekatan deskriptif. Lokasi penelitian berada di Dusun Jatisumber, Desa Watesumpak, Trowulan, Mojokerto. Teknik pengumpulan data diperoleh dari observasi non partisipan, wawancara terstruktur, serta dokumentasi. Hasil penelitian ini didapatkan bahwa penurunan pengrajin patung batu andesit di Dusun Jatisumber disebabkan karena insiden bom Bali 1 tahun 2002, tempat pembuatan patung cor di Dusun Jatisumber tahun 2005, serta krisis ekonomi global tahun 2008. Pengrajin yang tidak meneruskan usahanya dapat beralih profesi maupun menjadi pemahat patung batu andesit di tempat usaha lain, sehingga hanya tersisa beberapa dari pengrajin patung batu andesit yang memutuskan untuk bertahan. Adapun pengrajin yang bertahan menerapkan 10 strategi adaptasi untuk mengatasi kendala serta mempertahankan usaha patung batu andesit. Sebagaimana teori struktural fungsional dari Talcott Parsons bahwa penurunan pengrajin membentuk sistem pada usaha patung batu andesit, hal ini peranan yang dimiliki pengrajin serta pemahat saling berkaitan dalam sistem. Sehingga bagian dari AGIL dilakukan agar sistem dapat bertahan yang diantaranya meliputi: penentuan 10 strategi adaptasi (adaptation), strategi adaptasi diterapkan untuk mewujudkan tujuan (goal attainment), pelaksanaan strategi adaptasi melalui kerja sama (integration), menjaga usaha patung batu andesit dengan menerapkan strategi adaptasi (latency).Kata Kunci: Pengrajin, Strategi Adaptasi, Usaha Patung Batu Andesit